Stock Market Efficiency in Nepal: A Variance Ratio Test - Dangol, Jeetendra (NRB Economic Review, 2016)
The paper examines random-walk behaviour and weak-form market efficiency on daily and weekly market returns of All Share Price Index and nine sectoral indices in the Nepal Stock Exchange (NEPSE) using Lo and MacKinlay (1988) variance-ratio tests and corrected data as suggested by Miller et al. (1994). The study finds that the random-walk hypothesis is strongly rejected for weekly indices of the observed and corrected returns. It shows that market participants have opportunities to predict future price and earn abnormal returns from the Nepalese stock market. Whereas, overall and development banking sectors support the random-walk hypothesis in daily observed and corrected returns. It indicates that technical analysis may not be fruitful to earn excess returns in overall and development banking sectors.